Predicting Poststroke Pneumonia in Patients With Anterior Large Vessel Occlusion: A Prospective, Population-Based Stroke Registry Analysis - Schaller-Paule, Martin A.; Foerch, Christian; Bohmann, Ferdinand O.; Lapa, Sriramya; Misselwitz, Björn; Kohlhase, Konstantin; Rosenow, Felix; Strzelczyk, Adam; Willems, Laurent M. (Frontiers in Neurology, 2022)
Objective: To assess predictive factors for poststroke pneumonia (PSP) in patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO) of the anterior circulation, with special regard to the impact of intravenous thrombolysis (IVT) and endovascular treatment (EVT) on the risk of PSP. As a secondary goal, the validity of the A2DS2, PNEUMONIA, and ISAN scores in LVO will be determined. Methods: Analysis was based on consecutive data for the years 2017 to 2019 from the prospective inpatient stroke registry covering the entire federal state of Hesse, Germany, using the Kruskal-Wallis test and binary logistic regression. Results: Data from 4,281 patients with LVO were included in the analysis (54.8% female, median age=78 years, range=18–102), of whom 66.4% (n=2,843) received recanalization therapy (RCT). In total, 19.4% (n=832) of all LVO patients developed PSP. Development of PSP was associated with an increase in overall in-hospital mortality of 32.1% compared with LVO patients without PSP (16.4%; p<0.001). Incidence of PSP was increased in 2132 patients with either EVT (n=928; 25.9% PSP incidence) or combined EVT plus IVT (n=1,204; 24.1%), compared with 2149 patients with IVT alone (n=711; 15.2%) or conservative treatment only (n=1438; 13.5%; p<0.001). Multivariate analysis identified EVT (OR 1.5) and combined EVT plus IVT (OR 1.5) as significant independent risk factors for PSP. Furthermore, male sex (OR 1.9), age ≥65 years (OR 1.7), dysphagia (OR 3.2) as well as impaired consciousness at arrival (OR 1.7) and the comorbidities diabetes (OR 1.4) and atrial fibrillation (OR 1.3) were significantly associated risk factors (each p<0.001). Minor stroke (NIHSS ≤4) was associated with a significant lower risk of PSP (OR 0.5). Performance of risk stratification scores varied between A2DS2 (96.1% sensitivity, 20.7% specificity), PNEUMONIA (78.2% sensitivity and 45.1% specificity) and ISAN score (98.0% sensitivity, 20.0% specificity). Conclusion: Nearly to one in five stroke patients with LVO develops PSP during acute care. This risk of PSP is further increased if an EVT is performed. Other predictive factors are consistent with those previously described for all AIS patients. Available risk stratification scores proved to be sensitive tools in LVO patients but lack specificity.